Is SARS CoV 2 reinfection, a result of ineffective Antibody response? - Maharjan, Kripa (Journal of General Practice and Emergency Medicine of Nepal, 2020)
This is a case report of two patient who developed symptoms and retested positive for SARS COV-2 after being recovered from the same infection one month back. Reinfections will increase the case burden and delay herd immunity. Reinfection is possibly due to poor antibody response of the first infection. Poor antibody response is possibly due to mild infection with low viral load.